Single bacteria identification with second-harmonic generation in MoS2 - Kim, Young Chul; Jun, Seung Won; Ahn, Yeong Hwan (Biosensors and Bioelectronics, 2023)
Transition-metal dichalcogenides exhibit extraordinary optical nonlinearities, making them promising candidates for advanced photonic applications. Here, we present the microbial control over second-harmonic generation (SHG) in monolayer MoS2 and the identification of single-cell bacteria. Bacteria deposited on monolayer MoS2 induce a change in the SHG signal, in the form of anisotropic polarization responses that depend on the relative orientation of the bacteria with respect to the MoS2 crystallographic direction. The anisotropic enhancement is consistent with the presence of a tensile stress along the lateral direction of bacteria axis; SHG imaging is highly effective in monitoring biomaterial strain as low as 0.1%. We also investigate the ultraviolet-induced removal of single bacteria, through the SHG imaging of MoS2. By monitoring the transient SHG signals, we determine the rupture times for bacteria, which varies noticeably for each species. This allows us to distinguish specific bacteria that share habitats; SHG imaging is useful for label free identification of pathogens at the single cell levels such as E. coli and L. casei. This label-free detection and identification of pathogens at the single-cell level can have a profound impact on the development of diagnostic tools for various applications.
Keywords: Advanced photonics application; Bacteria identifications; Dichalcogenides; Harmonic generation imaging; Label-free sensing; Microbial control; Microbial strain; Optical nonlinearity; Single-cell level; Transition metal dichalcogenides; Bacteria; Label-free sensing; Microbial strain; Second harmonic generation; Transition metal dichalcogenides